Investigating challenges in Agile software development: a cross-country comparative analysis - Fissalma, Hanifa; Ferdinansyah, Alex; Purwandari, Betty (Institute of Advanced Engineering and Science, 2025)
Agile software development has been a significant methodology in software engineering for over two decades, offering enhanced adaptability to software requirement changes, improved delivery, and better quality. However, prevalent misunderstandings in Agile implementation have limited its benefits. Hence, this study investigates the challenges faced during Agile implementation. Initial analysis was carried out from cases in Indonesia, a leading country in the software industry within the Asia-Pacific region. Using Kitchenham’s systematic literature review (SLR) methodology, fourteen distinct obstacles were identified from a database of research reports on Agile software development in Indonesia. Subsequent interviews with Agile experts in the country were conducted to validate the SLR findings. The results emphasize the critical need for a top-down strategic approach, the active participation of senior management, and the essential roles of competent scrum masters or Agile coaches. A comparative analysis with reports from other developing countries Saudi Arabia, India, Malaysia, Brazil and developed countries the UK, Belgium, Singapore, and the USA reveals common challenges. They highlight the imperative for proactive upper management leadership to steer successful Agile adoptions, particularly in organizations with entrenched top-down practices and complex hierarchical systems.